Carotid artery disease and the risk of ischaemic stroke and coronary vascular events. - Rothwell, P (2000)
Information on the presence and extent of carotid arterial wall disease has significant prognostic value. Carotid artery stiffness, intima-media thickness, and early plaque formation are potentially useful predictors of the risk of both ischaemic stroke and coronary heart disease in asymptomatic populations. Early carotid arterial wall disease is also a useful predictor of coronary artery disease on angiography and subsequent coronary vascular events in populations at risk of coronary heart disease. More advanced carotid wall disease (carotid stenosis and plaque surface morphology) is predictive of both ischaemic stroke and coronary heart disease in high-risk populations with established cerebrovascular disease. Plaque characteristics on ultrasound, such as echolucency, may also have a prognostic value. However, in order to identify individuals with high risks of vascular events, this information must be combined with other clinical, laboratory, and imaging data. Ideally, large prospective cohort studies are required in which all these data are recorded and then combined using multivariate statistical modelling. Future studies should also determine the relationship between the various measures of carotid wall disease and the risk of stroke for the different subtypes of ischaemic stroke.